2021
DOI: 10.1155/2021/5561829
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Purification from Permanganate Ions by Sorption on the Ocimum basilicum Leaves Powder Modified by Zinc Chloride

Abstract: The powder of Ocimum Basilicum leaves was treated by zinc chloride (ZnCl2) and applied as a new and low-cost sorbent for extraction of permanganate anions (MnO4−) from liquid phase. The functional groups of the ring stretching vibration, –NH2 deformation, stretching of C-O, stretching of CH, and stretching of –NH were found in the sorbent of zinc chloride Ocimum basilicum leaves powder (ZCOBLP) at 1516.21, 1629.33, 1047.00, 2929.88, and 3294.93 cm−1, respectively. This adsorbent has 8.3 pHZPC, 117.27 m2·g−1 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(49 reference statements)
1
5
1
Order By: Relevance
“…10 is the thermodynamic fitting diagram, and the thermodynamic parameters are shown in Table S6 (ESI†). Δ H was positive for different temperatures and adsorbents, which indicated that the adsorption of Cu( ii ) and Pb( ii ) by NaA molecular sieves is a heat-absorbing process, 50 and the increase of temperature was favorable for the adsorption, which also confirmed our previous conclusions. Δ S indicates the degree of disorder in the adsorption system, and Δ S > 0 indicates that the adsorption process proceeds in the direction of increasing disorder.…”
Section: Resultssupporting
confidence: 89%
“…10 is the thermodynamic fitting diagram, and the thermodynamic parameters are shown in Table S6 (ESI†). Δ H was positive for different temperatures and adsorbents, which indicated that the adsorption of Cu( ii ) and Pb( ii ) by NaA molecular sieves is a heat-absorbing process, 50 and the increase of temperature was favorable for the adsorption, which also confirmed our previous conclusions. Δ S indicates the degree of disorder in the adsorption system, and Δ S > 0 indicates that the adsorption process proceeds in the direction of increasing disorder.…”
Section: Resultssupporting
confidence: 89%
“…It was indicating that the samples are typical mesoporous materials according to IUPAC classification, which reflects the occurrence of capillary condensation phenomenon in the pores. [ 50,51 ] These results are inconsistent with the observations obtained from the SEM images.…”
Section: Resultscontrasting
confidence: 63%
“…[ 56 ] It was demonstrated that the uptake capacity improved with the growing concentration of pollutants because when the concentration increases, the mass transfer resistance between the sorbent and sorbate was decreased which led to a consequential rise in the values of uptake capacity. [ 51,57 ]…”
Section: Resultsmentioning
confidence: 99%
“…The rise in Pb 2+ ions removal rate at low initial Pb 2+ ions concentration is caused by the adsorbent surface having enough open active sites. As a result of a lack of active sites on the adsorbent, the adsorption rate slowed down with increasing initial Pb 2+ ions concentration [ 49 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%